The next chapter: UiTM in pursuit of becoming a Globally Marketable University in modern pharmacognosy / Dr. Salfarina Ramli and Nik Aisyah Najwa Nik Mustaffa Shapri - Ramli, Salfarina; Nik Mustaffa Shapri, Nik Aisyah Najwa (Faculty of Pharmacy, 2023)
On 21st September 2023, 'Coffee Talk with Rozie - The Next Chapter' program extended an invitation to Dr. Salfarina Ramli as the distinguished panelist. The program which is hosted by the sixth Vice-Chancellor of Universiti Teknologi MARA (UiTM), Professor Datuk Ts. Dr Hajah Roziah Mohd Janor serves as an innovative platform to disseminate the expertise and dedication of UiTM staff to all UiTM stakeholders. Dr Salfarina is a lecturer in the field of pharmacognosy at the Faculty of Pharmacy UiTM. Her strong commitment to pharmacognosy research is well-depicted through international collaboration with researchers from Mae Fah Luang University, Thailand, and Universitas Airlangga, Indonesia. These collaborations encompass various aspects of pharmacognosy, covering both laboratory-based research and pedagogical pursuits. Entitled "UiTM in Pursuit of Becoming a Globally Marketable University in Modern Pharmacognosy", Dr. Salfarina shared her in-depth insights on various key questions of pharmacognosy and UiTM's aspirations in the evolving field. Dr. Salfarina succinctly described pharmacognosy as the knowledge of the biological activities of natural compounds derived from natural sources. It is a diverse field that contributes to the enhancement of human health. A firm comprehension of pharmacognosy among UiTM researchers is crucial to promote collaborations between different faculties. She also emphasized the significance of interdisciplinary collaboration and highlighted how combining knowledge from various fields can lead to ground-breaking discoveries.